PENGARUH KOMPETENSI DAN PENEMPATAN PEGAWAI TERHADAP KEPUASAN DAN KINERJA PEGAWAI - Ngebu, Wilfridus Djaga; Sintaasih, Desak Ketut; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.12.TAHUN 2018DO - 10.24843/EEB.2018.v07.i12.p05, 2018)
Organization expects to achieve a good performance. Organizational performance can be measured if the individual or group of employees has had had success criteria or standards set by the organization. Organizational performance is often not be optimal for several reasons including a lack of support for human resources quality. Perceived job satisfaction of the employees, as well as the placement the employees in the organization and work competencies possessed may have impacts on the achievement of employee performance and organizational performance. This study was conducted to access the influence of competency and placement of employees on satisfaction and performance of employees of the Department of Education, Culture, Youth and Sports (PKPO) in Ngada Regency. 66 employees are selected. Data were collected by questionnaires and the analyzed using path analysis. The results of the analysis prove that the competency and placement have positive and significant effect on job satisfaction and that the competency and placement have positive and significant impact on employee performance. It is also proved that job satisfaction has positive and significant impact on employee performance. Validation of the model shows the value of the coefficient of determination of 0.94, which means the performance variable is explained by competence, placements and job satisfaction of 94% and the remaining 6 % is explained by other factors beyond our model instance variables such as work environment, discipline, leadership and culture organization. Competence variable is proven affects the performance through satisfaction, but in influencing the performance, direct competence affect performance is more powerful compared to the competence affect performance through job satisfaction. Placement variable is proven affects the performance through satisfaction, but in influencing the performance, direct placement affect performance is more powerful compared to the placement affect performance through job satisfaction. The analysis concluded that the variable competence, placement and job satisfaction have positive and significant impact on the performance of the officer. In an effort to achieve an optimized organizational performance, it is recommended that further enhance the performance of the officer, the officer job satisfaction in the work should always get the attention of the organization. Placement officers in acting roles and responsibilities of the organization should also base on competence, experience and interest and continue to increase the competency of officers because of the competency of personnel adequate and appropriate organization standard, the performance and the organization's goals can be achieved.